Swimming-related complications during triathlon event - Alifrangis, A.; Suzan, M.; Kipps, C. (British Journal of Sports Medicine, 2021)
Background: The majority of serious medical complications within triathlons occur during the swim leg of the race. Race organisers and medics have a duty of care to ensure that their teams are prepared to rapidly identify, remove and treat swimmers in distress. Objective: To describe the incidence and causes for water rescue team extractions from the swim part of triathlon events. Design: Observational study. Setting Two large community-based mass-participation triathlon races held in the UK during the summer over 4 years between 2013-2016. Patients (or Participants) :All participants requiring intervention from the water rescue team were included in the study. Relay participants were excluded. Interventions (or Assessment of Risk Factors): Demographics including age, gender; and race factors including distance and wave size. Main Outcome Measurements: Participant demographics and reasons for intervention were recorded in water rescue team extraction logs. Outcomes of serious medical complications were recorded where available. Results: Race reports from 7 triathlons in the UK between 2013 - 2016 were analysed. 44,159 triathletes started the events, competing across swim leg distances of 400 m, 750 m and 1500 m. 232 competitors required extraction from the water (5.2/1000 starters). Those aged 30-34 were most likely to require extraction. There was no significant difference in extraction rates between male and female participants. 14.7% of extractions were due to breathing difficulties. Other reasons for extraction were tiredness (31%), cramp (12%) and injury (8%). Two male athletes suffered cardiac arrests in the water and required resuscitation. One later died in hospital. Conclusions: Serious medical complications in the swim leg of triathlons are rare but can be fatal. Water rescue and race medical teams must be adequately prepared to rapidly identify and intervene in such cases. Further research is needed to look at causes of breathlessness in injury in these events.